Pengaruh Bitcoin, Indeks Harga Saham Gabungan (IHSG), dan Harga Emas Terhadap Kinerja Keuangan Perusahaan Sekuritas (Jurnal Kendali Akuntansi, 2025)
Securities companies are one of the key pillars in the capital market system. The performance of securities companies can be influenced by dynamic market conditions, particularly the fluctuations of Bitcoin, Indonesia Composite Index (ICI), and gold prices. This study aims to analyze the influence of Bitcoin, ICI, and gold prices on the financial performance of securities companies in Indonesia. The financial performance is measured using the profitability ratio, Net Profit Margin (NPM). The sample consists of quarterly secondary data from 24 securities companies that meet the research criteria during the 2021–2024 period. The analytical method used is multiple linear regression after passing classical assumption tests. The results show that gold prices have a negative and significant effect on the NPM of securities companies, while Bitcoin and ICI had no effect. This indicates that an increase in gold prices tends to be followed by a decrease in the NPM of securities companies, and vice versa. This research is expected to assist the management of securities companies in formulating business strategies and risk management that are more responsive to fluctuations in Bitcoin, ICI, and gold prices.